Extraskeletal Myxoid Chondrosarcoma: Long-Term Survival in the Setting of Metastatic Disease - Karim Masrouha; Iqbal Multani; Om Bhatt; Michelle Ghert (Case Reports in Orthopedics)
Three cases of extraskeletal myxoid chondrosarcoma (EMC) in patients who presented with pulmonary metastases and were managed with long-term close observation without systemic intervention are presented. Follow-up imaging showed slow progression of their disease over several years, and the patients remained asymptomatic from their pulmonary metastases. This clinical experience provides insight into the natural history of the disease and suggests that some patients may experience long-term survival and remain asymptomatic even without systemic intervention, thereby improving their quality of life by avoiding potentially debilitating treatments.